2017
DOI: 10.3389/fimmu.2017.00697
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Antibody Replacement Therapy to Innate and Adaptive Immune Cells

Abstract: Intravenous immunoglobulin administered at replacement dosages modulates innate and adaptive immune cells in primary antibody deficiencies (PAD) in a different manner to what observed when high dosages are used or when their effect is analyzed by in vitro experimental conditions. The effects seem to be beneficial on innate cells in that dendritic cells maturate, pro-inflammatory monocytes decrease, and neutrophil function is preserved. The effects are less clear on adaptive immune cells. IVIg induced a transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
(68 reference statements)
0
22
0
2
Order By: Relevance
“…It provides passive immunity to many infectious agents including common coronaviruses that may share epitope specificity with SARS-CoV-2, as well as bacterial agents and endotoxins (including SEB). Furthermore, IVIG serves as an immunomodulator of both innate and adaptive immunity by multiple mechanisms (140).…”
Section: Initial Treatment Of Mis-c Involves High Dose Ivig and Aspirinmentioning
confidence: 99%
“…It provides passive immunity to many infectious agents including common coronaviruses that may share epitope specificity with SARS-CoV-2, as well as bacterial agents and endotoxins (including SEB). Furthermore, IVIG serves as an immunomodulator of both innate and adaptive immunity by multiple mechanisms (140).…”
Section: Initial Treatment Of Mis-c Involves High Dose Ivig and Aspirinmentioning
confidence: 99%
“…Few papers described the beneficial effect of high doses immunoglobulins administered in COVID-19 patients on improving symptoms, fever, and lymphopenia, although the selected patients were not affected by IEI [17]. It has been widely demonstrated that IVIG exert immunomodulatory effects on many inflammatory cells such as monocytes [18] and may also contain antibodies directed to other coronaviruses potentially cross-reactive with COVID-19 [19]. Due to the widespread and long-term circulation of human coronaviruses, and the pooling of plasma from thousands of donors for every lot, immunoglobulins might contain levels of antihuman seasonal coronaviruses antibodies.…”
Section: Immunoglobulin Replacementmentioning
confidence: 99%
“…The adaptive immune response develops slowly and needs two weeks to generate the most specific and effective defensive tools. However, the vast majority of PAD patients infected with SARS-CoV-2 did not show signs of hyper-activation of the innate immunity [3][4][5], an effect possibly due to the immunomodulatory effects on innate immune cells due to the regular use of polyvalent immunoglobulins [30], and a poor adaptive immunity. This pattern of immune responses resembles what we have already shown in asymptomatic immunocompetent subjects [36], and further demonstrated that a balanced cytokine production resulting from a functional but not hyper-reactive innate immunity and a poor adaptive immunity are the conditions associated with an early benign COVID-19 course.…”
Section: Discussionmentioning
confidence: 95%